Methodological guidelines for the professional adaptation of future teachers of dual education - Rikhsibay, Mamedov; Perizat, Parmankulova; Galymzhan, Karatayev; Zhanat, Nurzhanbayeva; Klara , Mukatai; Saule, Zholdasbekova (International Journal of Psychosocial Rehabilitation, 2020)
The methodological guidelines of professional adaptation of future teachers of dual education are considered: the main vectors of adaptation processes to dual learning, the mechanisms of professional semantic generation of duality and adaptation algorithms.